What do universities want from publishing? - Pinfield, Stephen (2004)
At a simple level, universities want publishing to support and further their mission to carry out research and teaching. However at a detailed level there are major differences within and between universities which mean there will be different wants and expectations of publishing. Bearing in mind these complexities, this paper examines universities' various requirements as producers, purchasers and consumers of publications. Some of the key wants of universities include impact, affordability, quality and access. The merits of the established system of subscription-based journal publishing and the emerging system of open-access publishing and dissemination are discussed in relation to universities' wants.